Your money or your life? Public support for health initiatives during the COVID‐19 pandemic. Issue 3 (30th May 2022) - Tranter, Bruce Keith
Abstract: While many Australians agree with the need for COVID‐19 restrictions and lockdowns, a vocal minority of citizens loudly voice opposition to government restrictions, characterised as impositions on 'free speech' and impacting the Australian economy. National data from the 2020/21 Australian Survey of Social and Attitudes and Tasmanian survey data enable an examination of those who support or oppose health initiatives aimed at minimising the impact of the pandemic. The majority of Australians believed government imposed restrictions were 'about right', although women were more likely than men to be concerned about the health implications of COVID‐19. Tasmanian data show that controlling for social background, those who prioritise the economy are less likely than those concerned about the health implications of COVID‐19 to wear masks in public, less likely to be tested in case they have to self‐isolate, less likely to check in, and less likely to be vaccinated. Alternatively, higher trust in university research, and trust in scientists as a source of information about COVID‐19 was positively associated with attitudes and behaviour designed to reduce the transmission of COVID‐19.